Digital Signature Using the SHA-512 Hash Function and the ElGamal Cryptographic Algorithm for Document Security - Adib Yusron Bokari; Meira Parma Dewi (Universitas Negeri Padang, 2025)
This study proposes a secure digital signature scheme using the SHA-512 hash function and the ElGamal cryptographic algorithm to ensure the authenticity and integrity of digital documents. The increasing reliance on digital communication has made document security a critical concern, as digital documents are vulnerable to unauthorised access, tampering, and fraud. To address this issue, a digital signature approach is implemented, leveraging the SHA-512 hash function to generate a unique message digest and the ElGamal algorithm to encrypt and decrypt the signature. The proposed system ensures that any alteration or modification of the document will result in a mismatch between the expected and actual hash values, thereby detecting potential security breaches. The combined use of SHA-512 and ElGamal algorithms provides a robust and secure digital signature scheme, guaranteeing the confidentiality, integrity, and authenticity of digital documents. This study demonstrates the effectiveness of the proposed scheme in preventing fraud and protecting digital documents from various security threats, making it a reliable solution for secure digital communication.